2019
DOI: 10.21776/ub.ijabs.2019.27.3.3
|View full text |Cite
|
Sign up to set email alerts
|

ANALYSIS OF THE EFFECT OF FIRM SIZE, FINANCIAL LEVERAGE, PROFITABILITY, DIVERSIFICATION ON MARKET RISK AND STOCK RETURN (Case Study of Manufacturing Companies in the Consumer Goods Industry Sector Listed on the Indonesia Stock Exchange in 2007-2016)

Abstract: The purpose of this study is to analyze the effect of firm size, financial leverage, profitability, diversification of market risk and stock returns. This research uses quantitative research methods. The population in this study is the consumption sector of manufacturing companies that are listed on the Indonesia Stock Exchange (IDX) during the observation period from 2007-2016. The sample technique using non probability sampling technique with purposive sampling method. The analysis technique used Partial Lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
2
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 8 publications
3
2
0
4
Order By: Relevance
“…It is also against Friede et al (2015) that discovered the consistent positive effects of sustainability performance (ESG) on the corporate financial performance after testing the different portfolio/non-portfolio corporate assets, corporate bonds, as well as regional and emerging markets. Meanwhile, the results are in line with Saeed, Belghitar, & Clark (2016) that showed the existence of a negative relationship between companies with political ties and corporate performance measured by profitability and growth as well as the study of Gengatharan (2020) and Agustin et al (2019) that found an insignificant impact of firm size on corporate value. It was, therefore, argued that the corporate value of large companies with significant assets cannot be improved significantly when those assets are not managed productively.…”
Section: Template Of Jurnal Economiasupporting
confidence: 84%
See 1 more Smart Citation
“…It is also against Friede et al (2015) that discovered the consistent positive effects of sustainability performance (ESG) on the corporate financial performance after testing the different portfolio/non-portfolio corporate assets, corporate bonds, as well as regional and emerging markets. Meanwhile, the results are in line with Saeed, Belghitar, & Clark (2016) that showed the existence of a negative relationship between companies with political ties and corporate performance measured by profitability and growth as well as the study of Gengatharan (2020) and Agustin et al (2019) that found an insignificant impact of firm size on corporate value. It was, therefore, argued that the corporate value of large companies with significant assets cannot be improved significantly when those assets are not managed productively.…”
Section: Template Of Jurnal Economiasupporting
confidence: 84%
“…This was further supported by a recent study that firm size affects profitability and corporate value, thereby, reflecting the corporate management's ability to optimize the management of its assets (Nursetya & Hidayati, 2021). Meanwhile, a contrary result showed that firm size did not have any substantial influence on the value of firms in the financial, industrial, and service sectors (Gengatharan, 2020), and this was also supported by the findings of Agustin, Dzulkirom, & Darmawan (2019) which showed an insignificant effect of firm size on stock returns as a proxy for firm value while studying Indonesian manufacturing companies in the consumption sector.…”
Section: Template Of Jurnal Economiasupporting
confidence: 56%
“…Traders only look at short-term profitable stocks, while good investors look at historical stock price movements to predict future profitable stocks. These results are in line with (Agustin, et al, 2019), In contrast to those produced by (Pais and Stork, 2013), (Laeven, et al, 2016) Firm size has an impact on risk and stock returns.…”
Section: Investment Risk Moderates the Effect Of Firm Size On Stock R...supporting
confidence: 82%
“…Then relationship between firm size, risk and return written by (Agustin, et al, 2019) Company Size has a negative and insignificant effect on Returns and Risk. Contrary to result (Pais and Stork, 2013), (Laeven, et al, 2016) company size has an impact on the risk and return of shares.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation